Astigmatism among Other Refractive Errors in Children of Southern Sri Lanka (Global Journal of Medical Research, 2015)
The main goal of this study was to find the problem of astigmatism among children with refractive errors who are were in the age group of 3 -14 years. A two stage screening process was envisaged and 5649 children were screened to find visual abnormalities and other defects. Of them, 1233 (21. 8%) were selected for second stage screening. The total ophthalmological manifestations found were 7.8% (78/1000). The analysis of different morbidities included refractive errors 6. 2% and other eye diseases 1. 6%. Among refractive errors 2.3% were unilateral and 3.9% were bilateral involvement. The prevalence of simple myopia was 1.65% and of hypermetropia was 0.95%. Yhe astigmatism found was 1.5% unilaterally out of 2.3 of total unilateral refractive errors. Bilateral astigmatism was 2.1% out of 3. 9% of total bilateral refractive errors. Findings indicate the existence of more astigmatic errors among Sri Lankan children either unilaterally or bilaterally.
Keywords: refractive errors; astigmatism; simple myopia; hypermetropia; screening